STRUKTUR IDIOMATIK VERBA BERPREPOSISI DALAM NOVEL YAUMA QUTILA AZ-ZAIM KARYA NAJIB MAHFUZ: ANALISIS SEMANTIK - , SYAHRI RAMADHAN SIREGAR ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research studies the idiomatic prepositional verb structure within the novel Yauma Qutila az-Zaâi>m by Naji>b Mah}fu>z. The aim of this research is to describe how much verb with prepositions that form idioms and full and partial idioms from thos verbs. This research use heed method or observational method with the basic techniques, that are tapping techniques and advanced techniques, that is noting techniques in provideng the data. While for the analysis, researcher used agih method with the basic techniques bagi unsur langsung (BUL) and advanced techniques and informal method in presenting the result of the data analysis. Based on the research, it is found that there are 105 data of idiomatic prepositional verb in the object. The details are as follows: (1) 7 idiomatic prepositional verb min, (2) 21 idiomatic prepositional verb ila>, (3) 12 idiomatic prepositional verb âan, (4) 30 idiomatic prepositional verb âala>, (5) 9 idiomatic prepositional verb fi>, (6) 23 idiomatic prepositional verb ba, and (7) 3 idiomatic prepositional verb lam. Moreover, from the data analysis, it is found that from 25 data out of 105, 21 of them are full idioms and the rest, not found partial idioms .